Genome Editing Technologies for Rice Improvement: Progress, Prospects, and Safety Concerns - Zafar, Kashaf; Sedeek, Khalid E. M.; Rao, Gundra Sivakrishna; Khan, Muhammad Zuhaib; Amin, Imran; Kamel, Radwa; Mukhtar, Zahid; Zafar, Mehak; Mansoor, Shahid; Mahfouz, Magdy M. (Frontiers in Genome Editing, 2020)
Rice (Oryza sativa) is an important staple food crop worldwide; to meet the growing nutritional requirements of the increasing population in the face of climate change, qualitative and quantitative traits of rice need to be improved. Stress-tolerant crop varieties must be developed with higher yields and increased adaptability to the changing climate. Genome editing and speed breeding have improved the accuracy and pace of rice breeding. New breeding technologies including genome editing have been established in rice, expanding the potential for crop improvement. Recently, other genome editing techniques such as CRISPR-directed evolution, CRISPR-Cpf1, and base editors have also been used for efficient genome editing in rice. Since rice is an excellent model system for functional studies due to its small genome and close syntenic relationships with other cereal crops, new genome-editing technologies continue to be developed for use in rice. In this review, we focus on genome-editing tools for rice improvement to address current challenges and provide examples of genome editing in rice. We also shed light on expanding the scope of genome editing and systems for delivering homology-directed repair templates. Finally, we discuss safety concerns and methods for obtaining transgene-free crops.